(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study examines contemporary foreign language teaching methods, highlighting the limitations of previous approaches in fulfilling current educational requirements. As globalization increases the need for multilingual proficiency, conventional approaches frequently fail to cultivate communicative ability, cultural awareness, and practical abilities. The study utilizes a mixed-methods approach, integrating classroom observations, surveys, interviews, and action research to evaluate the application of innovative pedagogical strategies, including Communicative Language Teaching, Task-Based Language Teaching, and Content and Language Integrated Learning. Materials comprise digital instruments, genuine resources, and task-oriented activities aimed at improving engagement and contextual learning. Research demonstrates substantial enhancements in student involvement, linguistic competency, and motivation when contemporary methodologies are utilized. Methods such as Content and Language Integrated Learning were notably helpful in enhancing cognitive abilities and practical language application. Digital and gamified technologies demonstrated efficacy in enhancing vocabulary memory and facilitating the practical application of language abilities. Nonetheless, obstacles such as unequal access to technology, classroom management, and the necessity for continuous teacher training persist as significant concerns.